(untitled) (Homiletic, 2009)
The paper demonstrates how Christian preaching can learn from Jewish preaching and Jewish (esp. Rabbinic) Scriptural interpretation. The rabbinic concepts of Haggadah and Halakhah can justify a new enthusiasm for the creative and precise, imaginative and meticulous exploration of the biblical word in Christian sermons.